Strengthening the Islamic Educational Values of Socialite Mothers with the 3t Method of Tahsin, Tahfidz and Tadabbur At The Ki Agus Arifin Talang Benih Curup Taklim Assembly - Febriyarni, Busra; Iswanto, Rahmat; Maryati, Ana; Tussakdiyah, Halima (Institut Agama Islam Negeri (IAIN) Curup, 2025)
The research carried out in the form of community service was carried out to strengthen the values of Islamic education in Ki Agus Arifin's Muslimah studies Tahsin program, to strengthen the values of Islamic education in Ki Agus Arifin's Muslimah studies Tahfidz program and to strengthen the values of Islamic education in studies. Muslimah Ki Agus Arifin Tadabbur program. Researchers use methods in the way PAR (Participatory Action Research) works. The results of this research note that the 3T strategy used by the Muslim women study team to strengthen the values of Islamic education for Rejang Lebong socialite mothers was tahsin, tahfidz and tadabbur Al-Quran. The tahsin practice carried out is to improve and improve the reading of the Al-Quran according to tajwid by jointly reading and discussing the rules of reading in surah al-kahf, so that when it is read the makhraj, mad and the characteristics of the letters will be improved. Meanwhile, tadabbur verse devotion is directed at strengthening Islamic education in its practice related to The main teachings of Islam are aqidah, muamalah and morals.